Motilitas dan Abnormalitas Spermatozoa Ayam Kampung yang Diberi Suplementasi Ekstrak Kulit Buah Naga - Dhian Ramadhanty; Angga Nugraha; Nurul Purnomo; Armayani M (JURNAL GALUNG TROPIKA, 2021)
This study aimed to determine the effect of dragon fruit peel extract on the motility and abnormalities of native chicken spermatozoa. The study was arranged experimentally using a completely randomized design consisting of 4 treatments and 3 replications. Before treatment, 12 native chicken were randomly divided into groups and adapted for 10 days with commercial feed and drinking water. The treatments were given orally for 8 weeks and consisted of P0 (control), P1 (1 ml dragon fruit peel extract), P2 (3 ml dragon fruit peel extract), and P3 (5 ml dragon fruit peel extract). Cement storage is carried out by the sequencing method. The quality of the collected sperm is tested in the laboratory. The parameters measured were microscopic sperm quality, namely sperm motility, and abnormalities. The results showed that dragon fruit peel extract had a significant effect on spermatozoa motility by increasing the percentage of motility but had no effect on spermatozoa abnormalities. Provision supplement of 5 ml dragon fruit peel extract gave the best results in increasing spermatozoa motility in native chickens.